HERITABILITY FOR GROWTH RELATED TRAITS IN GIANT FRESHWATER PRAWN (Macrobrachium rosenbergii) AT VARIOUS DEVELOPMENTAL STAGES AND CULTURE CONDITIONS ESTIMATED BY INTRACLASS CORRELATION - Imron Imron; Rommy Suprapto (Indonesian Aquaculture Journal, 2013)
Heritability estimates of commercially important traits are of important in order to seek the best strategy of selective breeding program to be implemented. A study aimed at estimating the magnitude of this parameter for growth related traits, expressed in wet weight (WW), total length (TL), and standard length (SL), has been carried out in giant freshwater prawn (GFP). Particular emphasis was given to investigate the effect of ages and culture conditions on the magnitude of the heritability estimates. Nineteen full-sib families were established through individual pair mating. The families, namely groups of offsprings derived from each mating pair were raised through three stages of rearing activities: first-stage nursery (40 days), second-stage nursery (70 days), and grow-out rearing (130 days). Heritability for growth at each stage was estimated through the method of full-sib analysis or intraclass correlation. Components of variance used to produce the heritability estimates were obtained through the method of analysis of variance. Results showed that heritability estimates varied with both ages and culture conditions. The heritability estimates (± standard errors) at 40 days for WW (0.69±0.151), TL (0.64±0.148), and SL (0.70±0.144) were higher than those observed at 70 days (WW = 0.24±0.15; TL = 0.22±0.15; and SL = 0.20±0.14) and 130 days (WW = 0.24±0.058; TL = 0.22±0.05; and SL = 0.20±0.60). A similar pattern was found with respect to the culture conditions. The estimates found in grow-out at lower stocking density (5 individual/ m2) days (WW = 0.24±0.058; TL = 0.22±0.05; and SL = 0.20±0.60) were higher than those observed at grow out at higher stocking density (20 individuals/m2) days (WW = 0.12±0.058; TL = 007±0.05; and SL = 0.14 ± 0.60). The possible causes of the observed patterns and implications that these findings may have on the breeding program of GFP are discussed.